Assessment of oxytocin level, glucose metabolism components and cutoff values for oxytocin and anti-mullerian hormone in infertile PCOS women - Bahia Namavar Jahromi; Mohammad Hossein Dabbaghmanesh; Pardis Bakhshaie; Mohammad Ebrahim Parsanezhad; Zahra Anvar; Mahshid Alborzi; Afsoon Zarei; Mina Bakhshaei (Taiwanese Journal of Obstetrics & Gynecology, 2018)
Objective: Comparing oxytocin level and some other parameters between infertile women with or without polycystic Ovary Syndrome (PCOS), to evaluate the correlation between oxytocin with anti-mullerian hormone (AMH), Body Mass Index (BMI) and insulin resistance (IR). Materials and methods: This cross–sectional study was performed on 80 PCOS and 81 non-PCOS women as the control group. Oxytocin, various hormones, Oral glucose tolerance test (OGTT) and Homeostatic model assessment of insulin resistance (HOMA-IR) were compared between two groups. Correlations between parameters were assessed by the spearman's rank correlation coefficient. Cutoff values for oxytocin and AMH in PCOS were calculated by the ROC-Curve and DeLong method. Results: The mean oxytocin level was statistically lower in the case group (p ≤ 0.001). The mean BMI, AMH, HOMA-IR, fasting insulin and insulin 2-h after 75-g glucose were significantly higher in the PCOS group. Oxytocin was negatively correlated to AMH when evaluated for all participants or only among controls. Moreover oxytocin was negatively correlated to HOMA-IR among all participants. However the relationship between oxytocin and BMI was not statistically significant. The calculated cutoff value for oxytocin was 125 ng/L and for AMH was 3.6 ng/mL in the PCOS group. Conclusion: The mean oxytocin level in the PCOS infertile women was lower than non-PCOS women. Oxytocin showed a significant reverse correlation with AMH and HOMA-IR. Keywords: Polycystic ovary syndrome, Oxytocin, Anti-mullerian hormone, Oral glucose tolerance test (OGTT)